Pandemic impacts on child development: A literature review (Research, Society and Development, 2023)
Objectives: To analyze how the COVID-19 pandemic affected children's mental health, as well as behavioral changes in child development. Methods: It consists of a bibliographic review study, in which a search was carried out in the databases: SCIELO, PubMed, Virtual Health Library (BVS), EbscoHost in the period of 3 years, between 2020 and 2022, in Portuguese and English. . 48 articles were selected, of which 28 were excluded for not meeting the proposed inclusion criteria, so that 20 studies were analyzed. Results: It was observed that during the period of isolation and social distancing, children were more likely to develop psychic and physical changes, such as increased use of screens, irritability, drop in school and cognitive performance, chronic and acute stress, anxiety, depression, sleep and appetite disorders, weight gain, sedentary lifestyle, irritability, fear, insecurity and impaired social interactions. Conclusion: The literature review found the incidence of damage to mental health as well as disorders in child behavior caused during the pandemic period. In this way, the possible impacts on child development and the importance of caring for children's demands accentuated by the pandemic are highlighted.